An integrated approach to understanding the architecture of DDX3-mediated HIV translation pre-initiation complex - Ward, Shannon Leigh (2024)
HIV transcripts contain highly structured 5′ untranslated regions (5′ UTR), necessitating a non-canonical translation pre-initiation complex (PIC), to allow ribosomes to bind and carry out translation. The PIC uniquely comprises the human DEAD-box RNA helicase, DDX3, bound directly to the trans-activation response (TAR) RNA stem loop of the 5′ UTR, with the addition of eukaryotic initiation factor 4G and poly(A) binding protein. Given its unique involvement in translation of HIV transcripts, the PIC makes an attractive drug target. This research aimed to resolve the high-resolution three-dimensional (3D) structure of the HIV translation PIC, to enhance understanding of its function and aid structure-based drug design for HIV therapeutics. In addition, the hypothesis that HIV Tat protein is a co-factor in PIC formation was investigated, because of its known interactions with DDX3 and TAR RNA.